Library ergonomics a case study of the cataloging workstations of selected universities in the Philippines - Lacsamana, Marlon T. (2002)
Ergonomics is the investigation of human physical and mental abilities and the application of the knowledge in products, equipment and artificial environment (Garner 1999). The science of ergonomics can greatly improve the working conditions of the catalogers since cataloging is admittedly a strenuous, monotonous task, with catalogers spending a huge amount of time confined in a restrictive workstation. Poor ergonomics would be equivalent to human or cognitive error, where problems can both be physical or mental.